Poesía, identidad nacional y educación: el aporte nerudiano (Educational Perspectives Magazine (REPED), 2023)
Through the exegesis of Pablo Neruda’s textual work, we looked into his social representation of Chilean identity, and its relationship with the educational system. Through his word and actions, the poet became a central agent of our national imaginary, becoming one of its constituent icons, both at the national and intemational levels. Therefore, we offer a series of didactic activities through which students can have access to understanding his life dedicated to poetry. This was done within the framework of the current educational reform through its Fundamental Objectives, as well as the pertinent and integrated curriculum areas.
Keywords: Pablo Neruda, Chilean Identity, Educational Reform.